Transient Phenomena in High Speed Bipolar Devices. Issue 1 (1998) - Obrecht, Michael S.; Heasell, Edwin L.; Vlach, J.; Elmasry, Mohamed I.
Abstract : A new numerical method is applied to the analysis of the charge partitioning in the quasi-neutral base of a BJT. The results show that the conventional, 1:2 collector/ emitter partitioning is not valid in general. High level injection increases the collector fraction, whilst fast switching decreases it.